VLADIMIRSKOE DEPOSIT (EASTERN SAYAN): AGE OF DYKE COMPLEXES AND LOCALIZATION FEATURES OF GOLD MINERALIZATION - E. V. Airiyants; B. T. Nharara; O. N. Kiseleva; D. K. Belyanin; P. A. Roschektaev; A. V. Travin; S. M. Zhmodik (Геодинамика и тектонофизика)
The Vladimirskoe deposit is one of the largest gold ore deposits in the southeastern part of the Eastern Sayan. This work is devoted to the localization of mineralized zones and the determination of the formation time of gold mineralization.The geological and structural analysis has shown that second-order discontinuous disturbances accompanied by zones of beresitization, calcification, sulfidization and dyke bodies are the main ore-controlling structures of gold mineralization. For the first time, the age of rocks of dyke complexes and ore mineralized zones of the deposit has been established by 40Ar/39Ar dating methods.